Adsorption of Cu(II) Ions from Aqueous Solutions using a Magnetite Biochar Composite Material - Ta'bi, Widi Aprilia; Taba, Paulina; Wahab, Abdul Wahid; Gappa, Maming; Zakir, Muhammad; Permatasari, Nur Umriani (Makara Journal of Science, 2025)
Water contamination from heavy metals, such as Cu(II) ions, poses severe threats to human health and the environment. This necessitates the development of efficient and eco-friendly treatment methods. In this study, a magnetite–biochar composite (MBC) was developed as an effective adsorbent for reducing Cu(II) ions from liquid waste. Biochar was produced through the pyrolysis of water hyacinth at 500 °C, while magnetite was synthesized using FeSO₄·7H₂O and FeCl₃·6H₂O with molar ratio of 1:2. The MBC was formed using a co-precipitation method and characterized by Fourier transform Infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Brunauer–Emmett–Teller, and vibration sample magnetometer instruments. FTIR analysis confirmed the presence of Fe–O bonds, and XRD detected Fe₃O₄ peaks, confirming the successful integration of magnetite into the composite. The MBC exhibited a surface area of 72.54 m²/g and a saturation magnetization of 19.10 emu/g. Optimal Cu(II) ion adsorption occurred at pH 6 and a contact time of 60 min. Adsorption kinetics followed the pseudo-second-order model, and isothermal analysis aligned with the Sips model, indicating an adsorption capacity of 75.73 mg/g. These results demonstrate MBC’s excellent potential as a sustainable and effective adsorbent for treating Cu(II)-contaminated wastewater, offering an environmentally friendly solution to heavy metal pollution.